A selenium@polypyrrole hollow sphere cathode for rechargeable lithium batteries1. Issue 26 (22nd March 2015) - Guo, Jing; Wen, Zhaoyin; Ma, Guoqiang; Jin, Jun; Wang, Weiqi; Liu, Yu
<x xml:space="preserve">Abstract</x> A selenium@polypyrrole hollow sphere composite cathode delivers a reversible specific discharge capacity of 400 mA h g−1 after 80 cycles at 0.2 C.